ASISTENSI MENGAJAR “ENGLISH FOR FUN” DI KECAMATAN LEIHITU, LEIHITU BARAT, DAN LEITIMUR SELATAN - Tanasale, Inggrit O; Retraubun, Aditya Samuel; Mantulameten, Wenny E (Universitas Pattimura, 2023)
The basic and main secondary education are the foundations to teaching English for students. It is, however, inevitable that the geographical factor or a region highly affects the access to sufficient education and infrastructure in terms of teching English. As a response to this necessity, the Teaching Assistance Program, English for Fun, was designed to strengthen the capacities of English teachers. The program focuses on learning vocabularies from descriptive text. The undertaken approach was through Total Physical Response (TPR) methods with songs, games, and pictures. During the implementation at several schools, the students enjoyed these activities. In the end, these activities gave input to the teaching materials made by the team.